Assessment Of Indoor Particulate Matter (Pm2.5) In Newly Renovated Rooms At School Of Civil Engineering Building , Usm - Jamaludin, Nur Faizah (Universiti Sains Malaysia, 2022)
Indoor air quality is considered as one of the main concern for the human’s health especially during Covid-19 pandemic since people stay indoor more often compare to outdoor. Four newly renovated rooms in School of Civil Engineering buildings, USM, Penang were selected as a study area in this research. It is expected to be contaminated with pollutions and particulate matter due to the renovation works and contaminant sources from occupants. Hence, a monitoring is required to identify the PM2.5 concentration in the rooms and compare the level with air quality guideline from WHO. The monitoring was carried out involving two monitoring sessions for each room which was during semester break and ongoing semester. Concentration of PM2.5, temperature and relative humidity data were obtained using optical direct-reading monitor (ODRM) equipment of E-Sampler 9800 model and analyzed using SPSS software and Microsoft Excel. It was found that the average PM2.5 concentration for each monitoring session conducted at all selected rooms were between 3.038 μg/m3 to 22.731 μg/m3. The result showed that there were increase of PM2.5 concentration when the number of occupancy increase. PM2.5 concentration in all rooms were within the guideline from WHO which is 15μg/m3 except for Tetupai Lounge during semester break. Considering that the room was still under renovation during the monitoring, so the air quality in the room is still in good condition. Based on the result analysed using Pearson Correlation, the contribution of the meteorological sources such as temperature and relative humidity have a correlation with PM2.5 concentration. In conclusion, the occupancy and type of activities effects PM2.5 concentration. In addition, the indoor air quality in the newly renovated rooms were considered in good condition and safe to human’s health.